2021
DOI: 10.1002/ajp.23229
|View full text |Cite
|
Sign up to set email alerts
|

Temporal consistency and ecological validity of personality structure in common marmosets (Callithrix jacchus): A unifying field and laboratory approach

Abstract: Personality in animals has been extensively researched in recent decades. Temporal consistency of behaviors is almost always part of the personality definition and is usually explored in several different testing sessions or observation periods. However, it is still unclear whether the obtained personality constructs are stable across several years, which might be especially important for long-living animals, such as primates. Further, little is known on whether the personality structures obtained in the labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 117 publications
1
12
0
Order By: Relevance
“…The problems that affect human studies that purportedly find higher-order personality factors were absent in the present study: each animal was rated by two or three keepers, the correlations among latent variables were considerable, and adjusting for rater effects increased rather than decreased some interfactor correlations. Nevertheless, because second-order factors were not identified in other studies of common marmosets [ 13 , 17 , 31 , 44 ], including one that included 77 of the same animals, prior to interpreting the meaning of this phenomenon, we urge an attempt to replicate these findings and an analysis of similar data using more flexible modeling techniques [e.g., 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems that affect human studies that purportedly find higher-order personality factors were absent in the present study: each animal was rated by two or three keepers, the correlations among latent variables were considerable, and adjusting for rater effects increased rather than decreased some interfactor correlations. Nevertheless, because second-order factors were not identified in other studies of common marmosets [ 13 , 17 , 31 , 44 ], including one that included 77 of the same animals, prior to interpreting the meaning of this phenomenon, we urge an attempt to replicate these findings and an analysis of similar data using more flexible modeling techniques [e.g., 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…One reason for why a low level of between-subjects variance may come is that unmeasured influences, for example how animals are housed or bred, overwhelms, or makes it difficult to observe or perceive, individual differences in one or more traits. Recent findings that appear to rule out this possibility come from a study that found the same structure in laboratory-housed and wild common marmosets [ 44 ]. However, because the captive and wild groups lived in family groups, that study could not exclude the possibility that being raised in other kinds of groups might affect personality structure.…”
Section: Introductionmentioning
confidence: 99%
“…The problems that affect human studies that purportedly find higher-order personality factors were absent in the present study: each animal was rated by two or three keepers, the correlations among the latent variables were considerable, and adjusting for rater effects increased rather than decreased some correlations among factors. Nevertheless, because second-order factors were not identified in other studies of common marmosets [13, 17, 31, 44], including one that included 77 of the same animals, prior to interpreting the meaning of this phenomenon, we urge an attempt to replicate these findings and an analysis of similar data using more flexible modeling techniques [e.g., 11].…”
Section: Discussionmentioning
confidence: 99%
“…A low level of between-subjects variance may come about when unmeasured influences, for example in how animals are housed or bred, overwhelm or make it difficult to observe or perceive individual differences in one or more traits. However, a study that compared common marmosets that lived in a laboratory to those that lived in the wild [44] suggests that this does not happen. A low level of between-subjects variance may also come about because the personalities of individuals conform to that of their group [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation